L’autonomia decisionale della persona nelle situazioni di vulnerabilità, di debolezza e di razionalità limitata: iniziali riflessioni a margine della sentenza n. 50 del 15 febbraio 2022 della Corte costituzionale (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. L’iter procedurale del giudizio di ammissibilità costituzionale dei referendum abrogativi - 3. La sentenza della Corte costituzionale che ha dichiarato non ammissibile il referendum abrogativo sull’art. 579 c.p. (‘Omicidio del consenziente’) - 4. Le buone ragioni della prudente decisione assunta dai Giudici costituzionali - 5. Conclusioni.Decision-making autonomy of the person in situations of vulnerability, weakness and limited rationality: initial reflections on the sidelines of sentence no. 50 of 15 February 2022 of the Constitutional CourtABSTRACT: The Authors, starting with the decision of the Italian Constitutional Court which found the referendum to abrogate art. 579 c.p. (Murder of the consenting party), address, in a practical perspective, the question of the decision-making autonomy of the person in situations of vulnerability, weakness and limited rationality. Of the referendum question, they underline its cloudiness and ambivalence before analyzing the strengths of the decision that has finally given prominence to the many situations of fragility and vulnerability of the person not always and only due to the existence of an infirmity of mind. With all the practical consequences that derive from it for the care professionals to whom these people ask not only respect but rigorous guarantees of public protection.